The lizard - Borges, J. 1935-; Caistor, Nick; Caistor, Lucia (Seven Stories Press, Triangle Square Books for Young Readers, 2019)
"When a lizard appears in the neighborhood of Chiado, in Lisbon, it surprises passers-by, and mobilizes firefighters and the army"--